Pertumbuhan Misellium Bibit F1 Jamur Tiram(Pleurotus Ostreatus ) Dan Jamur Merang (Volvariella Volvaceae) Pada Media Biji Koro Benguk Dan Media Biji Koro Pedang Dari Bibit F0 Singkong - Hariyati, Hariyati; , Dra. Suparti, M.Si (2017)
Koro benguk and koro pedang have high carbohydrate and protein content. Lime serves to regulate the pH of mold growth medium. The purpose of this research is to know the growth of mislead of F1 seeds of oyster mushroom and mushroom which grown on coro bean medium medium and medium of koro sword. Type of research used in the form of experiment with Random Design Complete (RAL) method of factorial pattern consisting of 2 factors. Factor 1 type of media: M1 (100 g koro benguk seed), M2 (koro pedang seed 100 g). Factor 2 seeds F0: J1 (seeds F0 cassava oyster mushroom), J2 (seeds F0 cassava mushroom). Parameters measured were speed, density and growth thickness of misellium. Data were tested by quantitative descriptive analysis. Based on the results of speed, density, and growth thickness of the most rapid misellium in mushroom with the medium of koro pedang that is 12.6 cm, very thick meeting, and growing bushy while the slowest growth of misellium in mushroom merang with medium koro benguk 3 , 6 cm, tightly fit, and grow thin evenly. Keywords: Koro benguk, koro pedang, F1 seeds, mycelium growth.